The Effect of Neuroepo on Cognition in Parkinson’s Disease Patients Is Mediated by Electroencephalogram Source Activity - Bringas Vega, Maria L.; Pedroso Ibáñez, Ivonne; Razzaq, Fuleah A.; Zhang, Min; Morales Chacón, Lilia; Ren, Peng; Galan Garcia, Lidice; Gan, Peng; Virues Alba, Trinidad; Lopez Naranjo, Carlos; Jahanshahi, Marjan; Bosch-Bayard, Jorge; et al. (Frontiers in Neuroscience, 2022)
We report on the qEEG and cognitive effects of Neuroepo in Parkinson's disease (PD) patients from a double-blind safety trial (https://clinicaltrials.gov/ number NCT04110678), Neuroepo, a new erythropoietin (EPO) formulation with a low sialic acid content, that had satisfactory results in animal models and tolerance in healthy participants and PD patients. In this study twenty-six PD patients were assigned randomly to Neuroepo (n=15) or placebo (n=11) groups to test the tolerance of the drug. Besides, outcome variables were measured by neuropsychological tests and resting-state source quantitative EEG (qEEG) at baseline and six months after administering the drug. Probabilistic Canonical Correlation analysis was used to extract latent variables for the cognitive and for qEEG that shared a common source of variance. We obtained canonical variates for cognition and qEEG with a correlation of 0.97. Linear Mixed Model analysis showed significant positive dependence of the canonical variate cognition on the dose and the confounder educational level (p=0.003 and p=0.02, respectively). Addtionallly, in the meditation equation, we found a positive dependence of cognition with qEEG for (p=<0.0001) and with dose (p=0.006). Despite the small sample, both tests were powered over 89%. A combined mediation model showed that 66% of the total effect of the cognitive improvement was mediated by qEEG (p=0.0001) with the remaining direct effect between dose and cognition (p=0.002), due to other causes. These results suggest that Neuroepo has a positive influence on cognition in PD patients and that a large portion of this effect is mediated by brain mechanisms reflected in qEEG.